Impact of Internal and External Factors on Non-Performing Financing in Indonesia’s Islamic Commercial Banks - Firginia Amanda; Any Eliza; Rahmat Fajar Ramdani (Department of Islamic Banking, 2025)
Purpose–This study examines how external factors like inflation, FDR, and CAR affect non-performing financing in Indonesian Sharia commercial banks. Methodology—Using a quantitative methodology, this study examined Islamic commercial banks registered with the Financial Services Authority (OJK) over a five-year observation period, from 2019 to 2023. Purposive sampling was used to choose the study’s sample, which included ten Islamic commercial banks that met the requirements. The data analysis technique employed is panel data linear regression analysis with Eviews 13. Findings – Based on the results of research and analysis, it was concluded that partially FDR and CAR variables had a significant negative effect on NPF. In contrast, inflation variables did not affect NPF. Moreover, variable FDR, CAR, and inflation do not impact NPF. Implications – This study suggests that Islamic commercial banks should focus on internal factors, particularly the Financing to Deposit Ratio and Capital Adequacy Ratio, when managing Non-Performing Financing. An increase in FDR and a decrease in NPF indicate the importance of efficient liquidity management and strong capital to maintain the quality of financing assets. Originality—The study analyzed the effect of Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), and inflation on Non-Performing Financing (NPF) at Sharia commercial banks in Indonesia from 2019 to 2023. While FDR and CAR have a significant negative effect on NPF, and inflation has no effect, the study’s novelty lies in its simultaneous evaluation of all three variables, which collectively have no significant impact on NPF.